Addendum to “FPBH: A feasibility pump based heuristic for multi-objective mixed integer linear programming” [Comput. Oper. Res. 112 (2019) 104760] - Tricoire, Fabien; Mahmoodian, Vahid; Charkhgard, Hadi (Computers & operations research, 2022)
This is an addendum to the article ’Pal, A. and Charkhgard, H, “A feasibility pump based heuristic for multi-objective mixed integer linear programming”, Computers & Operations Research 112:104760, 2019. In that work, a comparison was made to another method – a multi-directional local search. This was done using a pre-existing code. After the above work was published, evidence emerged that the mentioned pre-existing code contained a bug. In this addendum note, that bug is corrected and updated comparative results are provided. •There was a then-unknown bug of third-party code.•A small portion of previously published result were affected by the bug.•We fix this bug and provide updated results.